As dimensões geográficas dos arranjos produtivos locais - Fuini, Lucas Labigalini [UNESP] (My University, 2014)
This article aims to further discuss the Local Productive Arrangements (APLs), considering some geographical visions thinking about spatial configuration and the economic and social processes that characterize them, configuring a wide range of territorialities and productive territories that mark the landscape current Brazilian. In this sense, APLs are present today in both the figure of those who study analytical concept for regional development, and as a public policy supporting networks and supply chains in their territorial bases, especially small businesses. Thus, this arrangements can be read, geographically, as territorial productive specializations that are configured in spatial circuits of production, integrated with other regions, localities and supply chains through the morphology of networks and districts and grounded in networks of urban networks of material and immaterial flows which are bringing urban centers of different sizes. Considering the multidimensionality of the subject, the clusters have certain weaknesses in terms of their assumptions and perspectives, especially the limitations of the tool if designed just for resources and policies applied at the local level. Suggest the approach of a “geography of APLs” is to seek treat it from a territorial and socio reading.
The geographical dimensions of local productive arrangements